Cholesteatoma in children and adults: are there really any differences?. Issue 7 (18th June 2018) - Jackson, R; Addison, A B; Prinsley, P R
Abstract: Background: Cholesteatoma is widely considered to be more aggressive in children than adults, yet few studies have directly compared the operative findings and surgical outcomes between these two groups. This study aimed to assess differences between childhood and adult cholesteatoma. Methods: The operative caseload of a single consultant surgeon was reviewed between January 2006 and May 2017 using the online Common Otology Audit database. Extracted data were categorised according to patient age (children, aged below 16 years, and adults, aged 16 years or over) and compared. Results: This study included data from 71 operations on children and 281 operations on adults, performed for cholesteatoma. Childhood cholesteatoma demonstrated significantly more extension (into the sinus tympani, mastoid antrum and mastoid air cells) and ossicular erosion (of the malleus, incus and stapes superstructure) compared to adults. No significant differences were seen in revision rates, post-operative complications or hearing gain. Conclusion: Childhood cholesteatoma was more extensive and destructive compared to adults, representing a more aggressive disease in this cohort.